Acute pyelonephritis during pregnancy: a systematic review of the aetiology, timing, and reported adverse perinatal risks during pregnancy - Grette, Katherine; Cassity, Sarah; Holliday, Nicolette; Rimawi, Bassam H (Journal of obstetrics and gynaecology, 2020)
We performed a comprehensive systematic review of acute pyelonephritis in pregnancy using PubMed, SCOPUS, ClinicalTrials.gov, and Ovid from inception to April 2018. About 7796 references were screened for inclusion, and 52 references from 1908 to 2017 were included. One hundred seven cases of acute pyelonephritis in pregnant women were reviewed. Gestational age at diagnosis was reported as 2 (2%), 43 (40%), and 51 (52%) during the first, second, and third trimesters, respectively. Maternal complications included sepsis (49%), acute respiratory distress syndrome (47%), anaemia (33%), acute kidney injury (10%), renal abscess (6%), and death (6%). 25 preterm deliveries (23%), 6 intrauterine foetal demises (6%), 4 spontaneous abortions (4%), and 8 neonatal intensive care unit admissions (7%) were reported. Microorganisms cultured included (51%), (8%), (5%), (5%), (4%), and (3%). Early diagnosis and management led to fewer complications.Impact statement Acute pyelonephritis during pregnancy can lead to adverse pregnancy outcomes and in this article, we highlight the most common outcomes previously reported. Previous studies have reported maternal adverse outcomes and only very few stressed on fetal/neonatal outcomes. The results add that not only is maternal morbidity/mortality is increased, but also increases adverse outcomes for the fetus/neonate, such as preterm delivery and fetal/neonatal demise. The implications from this article serve to increase a medical providers knowledge on how to appropriately counsel pregnant women with acute pyelonephritis. In addition, future research can aim to understand why pregnant women are more prone to morbidity and mortality compared to nonpregnant women.